Reklamasi Teluk Jakarta Ditinjau dari Perspektif Ekofeminisme - Restu Rahmawati; Firman Firman (ARISTO, 2019)
This paper discuss about the reclamation of Jakarta Bay from the perspective of ekofeminisme. The reason the writerchooses this issue, because of the need to emphasize the environmental aspect paired with ekofeminisme in development policy programs that have been done especially the development done over the ocean. The issues to be raised in this research question about how the policy of Jakarta Bay reclamation is viewed from the perspective of ekofeminisme as well as to know what factors push and obstruct Jakarta Bay reclamation policy. The research method used in this research is qualitative research method with case study approach. In order to obtain data in this study, researchers will use primary and secondary data sources. The results of this study indicate that the development of Jakarta Bay reclamation has not been in accordance with the perspective of ekofeminisme. This is because the reclamation of Jakarta Bay is still concentrated on economic matters only, and has not yet realized sustainable development. Thus, stakeholders are expected to apply an ecofeminism perspective to the Jakarta Bay reclamation development policy to avoid a global ecological crisis and environmental degradation. Feminism replied that the energy of femininity and not masculinity, has the potential to preserve the environment.